'Twas the night before Christmas on Sesame Street - Jaine, Lillian; Mathieu, Joe 1949-; Moore, Clement Clarke 1779-1863. (Naperville, Illinois : Sourcebooks Jabberwocky, 2018)
"It's the night before Christmas, and Cookie Monster is about to get a surprise visit from Santa!"--Page 4 of cover.
107403
Keywords: Moore, Clement Clarke -- 1779-1863.; Children's poetry, American; Christmas poetry; American poetry; Parodies; Adaptations; Fiction; Stories in rhyme; Juvenile works; Narrative poetry; Christmas poetry; Christmas fiction; Fiction